2022
DOI: 10.3389/fmed.2022.1051448
|View full text |Cite
|
Sign up to set email alerts
|

Fatality rate, risk factors, and functional decline in peritoneal dialysis patients with coronavirus disease 2019: A nationwide cohort study

Abstract: BackgroundThe fatality rates and factors associated with death from coronavirus disease 2019 (COVID-19) in hemodialysis patients have been extensively investigated. However, data on peritoneal dialysis (PD) patients remain scarce.Materials and methodsIn this nationwide cohort study, we assessed the 28-day COVID-19-related fatality rate in PD patients between August 2021 and July 2022 using data from the InCov19-PD registry. Predictors associated with death were evaluated using a multivariable Cox regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
2
1
Order By: Relevance
“…The most common symptoms were cough, followed by fever, myalgia and sore throat, similar to the symptoms in the general population. The rates of hospitalisation (16.2%) and mortality (3.8%) were lower than those in previous studies which reported a hospitalisation rate of 33-58% and a mortality rate of 23-52% [11][12][13][14]18,27,28 in dialysis patients with COVID-19, perhaps owing to the lower severity of the Omicron variant and the protection from vaccines. 29,30 However, these rates are still much higher than those reported in the general population (reported hospitalisation rate of approximately 2% and mortality rate of 0.1%), 8,31,32 confirming the poor outcome of COVID-19 in the PD population.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The most common symptoms were cough, followed by fever, myalgia and sore throat, similar to the symptoms in the general population. The rates of hospitalisation (16.2%) and mortality (3.8%) were lower than those in previous studies which reported a hospitalisation rate of 33-58% and a mortality rate of 23-52% [11][12][13][14]18,27,28 in dialysis patients with COVID-19, perhaps owing to the lower severity of the Omicron variant and the protection from vaccines. 29,30 However, these rates are still much higher than those reported in the general population (reported hospitalisation rate of approximately 2% and mortality rate of 0.1%), 8,31,32 confirming the poor outcome of COVID-19 in the PD population.…”
Section: Discussioncontrasting
confidence: 64%
“…10 A cohort study involving 1,487 PD patients between August 2021 and July 2022 in Thailand showed that the predictors of COVID-19-related death in PD patients were similar to those in haemodialysis patients, including vaccine, corticosteroid therapy, delta variant and need for respiratory support. 11 Other studies with smaller sample sizes showed a significant association between mortality and age, comorbidities, PD vintage, serum albumin, d -dimer levels, need for hospitalisation and hospital-acquired infection in PD patients with COVID-19. 12 14…”
Section: Introductionmentioning
confidence: 93%
“…To our knowledge, only one study has examined the impact of different variants on clinical outcomes in PD patients. In that paper, Chuengsaman et al reported that infection with the SARS‐CoV‐2 Delta variant in PD patients was associated with an increased risk of COVID‐related death compared to infection with the Omicron variant; the hazard ratio for death due to Delta compared to Omicron variant infection was 2.23 [30]. More research is warranted to further elucidate this important topic.…”
Section: Case Series and Cohort Studiesmentioning
confidence: 99%